Automated sand gravity filter system - Dube, Busani (Midlands State University, 2018)
Sand gravity filters can be automated to suit your requirements. Be it industrial or domestic this model can be implemented with ease. This research is mainly focused on getting sand gravity filters in industries automated using measurable variables like flow and level. The controls are based mainly on monitoring the filter tank level versus the outlet and inlet flows. Inlet flow and outlet flow are regulated to maintain a certain level beyond which the filter tank will be deemed flooding. With controlled flow certain levels in the filter tank signal clogging of the filters which will require cleaning using a backwash process. This process requires starting and stopping of pumps and air blower, hence using sensors and controllers the system can be automated.